IMPLEMENTASI TANGGUNG JAWAB PELAKU YANG TELAH DIPUTUS DENGAN HUKUMAN MATI ATAS PEMENUHAN HAK RESTITUSI ANAK YANG MENJADI KORBAN TINDAK PIDANA PERSETUBUHAN - Erwan H. Mokoginta (PT. Hasba Edukasi Mandiri, 2026)
This study aims to analyze the implementation of restitution rights for children who are victims of statutory rape, with a case study of Decision Number 86/Pid.Sus/2022/PT.Bdg. Restitution is a form of legal protection provided to child victims of crime to compensate for material and/or immaterial losses, including physical and psychological suffering, as well as the social impact caused by the crime. The research method used is normative juridical with a legislative and case approach. The research data was obtained through a literature study of laws and regulations, court decisions, and relevant legal literature. The results of the study show that even though the court has imposed a restitution obligation on the perpetrator, the fulfillment of the right to restitution for child victims has not been optimal, especially in cases where the perpetrator has been sentenced to death. This situation raises legal issues regarding the effectiveness of restitution enforcement and the certainty of fulfilling the rights of victims. Therefore, it is necessary to strengthen the restitution enforcement mechanism and harmonize regulations to ensure legal protection and the restoration of the rights of child victims of statutory rape.